The Influence of Entrepreneur Education and Self Efficacy on Students' Entrepreneurial Behavior through Planned Behavior as an Intervening Variable - Rachma, Alivia Maulidha; Hakim, Luqman; Surjanti, Jun (Electronic Journal of Education, Social Economics and Technology, 2024)
The importance of education as part of the process for individuals to find their identity in society. Education is considered the basis for direct transition to the labor market, besides it also plays an important role in creating and developing an entrepreneurial spirit so that Entrepreneurship education is carried out to encourage students in building business ideas and managing businesses. Students as representatives of the young generation of Indonesia can hone their experiences and be motivated to become entrepreneurs. This study was conducted to determine the Effect of Entrepreneur Education and Self Efficacy on Student Entrepreneurial Behavior Through Planned Behavior as an Intervening Variable using quantitative methods through the SPSS application. The population in this study was 320 students, but by using the Slovin formula as a guide, the researcher obtained a sample of 84 students. Entrepreneur education, Self efficacy, and Planned behavior possessed by students have been shown to have an effect on entrepreneurial behavior. Self efficacy has an effect on entrepreneurial behavior through planned behavior as an intervening variable with a significant and positive value.